Модели формального представления предметной области для экспертных систем - Судаков, Борис Николаевич; Пантелеева, Н. А. (НТУ "ХПИ", 2012)
В статье рассматривается проблема правильного и наиболее полного представления знаний конкретной предметной области и способы ее решения. Для решения данной проблемы в области систем искусственного интеллекта используются четыре модели представления знаний. Статья предоставляет детальный обзор этих моделей, их достоинств и недостатков. Определена и обоснована необходимость использования нескольких моделей для более точной формализации и более полного представления предметной области.

The paper under discussion covers the problem of correct and full presentation of the knowledge in a particular area. The approach to the problem is based on usage of models of knowledge representation. There are four models of knowledge representation used in artificial intelligence systems. The aim of the article is the introduction of these models and presentation of their drawbacks and benefits. After a closer investigation of the problem the following conclusion was made – in order to fully represent the area of knowledge it is required to use models of knowledge representation in complex.
Keywords: логическая модель; продукционная модель; семантические сети; фреймы; слоты; particular area; logical model; production model; semantic web; frames